2021
DOI: 10.1097/cmr.0000000000000736
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the development of immune related adverse events in metastatic melanoma treated with PD -1 inhibitors

Abstract: Some clinical trials have described improved outcomes in patients who develop immune-related adverse events (irAEs) while receiving immune checkpoint inhibitors for advanced melanoma. It is unknown if this effect would be seen in a real-world population. This is a single-center retrospective analysis of all patients receiving singleagent PD-1 inhibitor for unresectable stage III or stage IV melanoma between 2012 and 2018. The majority of patients had cutaneous melanoma and were elderly (put in median and range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Of the included studies, 46 were retrospective ( 13 17 , 32 , 34 , 35 , 39 , 41 , 43 52 , 54 , 55 , 57 , 59 72 , 74 78 , 82 85 ), 13 were prospective ( 18 , 33 , 36 38 , 40 , 53 , 56 , 58 , 73 , 79 81 ) (including four studies that extracted data from clinical trials ( 18 , 33 , 73 , 79 )), and one included both retrospective and prospective data ( 42 ). All included studies assessed the relationship between the presence of irAEs and prognosis (12 of them examined the effect of irAE grades ( 14 , 37 , 45 , 57 , 58 , 68 , 71 , 73 , 76 , 82 , 84 , 85 )), 18 studies assessed endocrine irAEs (any, thyroiditis, or hypophysitis) ( 32 , 34 , 44 , 46 48 , 51 , 55 , 56 , 60 , 68 70 , 73 , 76 , 78 , 81 , 85 ), five assessed pulmonary irAEs ( 32 , 34 , 46 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the included studies, 46 were retrospective ( 13 17 , 32 , 34 , 35 , 39 , 41 , 43 52 , 54 , 55 , 57 , 59 72 , 74 78 , 82 85 ), 13 were prospective ( 18 , 33 , 36 38 , 40 , 53 , 56 , 58 , 73 , 79 81 ) (including four studies that extracted data from clinical trials ( 18 , 33 , 73 , 79 )), and one included both retrospective and prospective data ( 42 ). All included studies assessed the relationship between the presence of irAEs and prognosis (12 of them examined the effect of irAE grades ( 14 , 37 , 45 , 57 , 58 , 68 , 71 , 73 , 76 , 82 , 84 , 85 )), 18 studies assessed endocrine irAEs (any, thyroiditis, or hypophysitis) ( 32 , 34 , 44 , 46 48 , 51 , 55 , 56 , 60 , 68 70 , 73 , 76 , 78 , 81 , 85 ), five assessed pulmonary irAEs ( 32 , 34 , 46 ...…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies assessed the association between the occurrence of skin irAEs and OS in patients with melanoma ( 32 , 34 , 38 , 42 , 46 48 , 51 , 53 , 54 , 56 , 62 64 , 73 , 74 , 76 , 79 , 81 , 85 ), while12 assessed the association with PFS ( 32 , 34 , 38 , 42 , 47 , 54 , 62 , 64 , 76 , 79 , 81 , 85 ). Pooled analysis showed that, among patients with melanoma treated with ICIs, those who had skin irAEs had a significant advantage in OS (pooled HR, 0.59; 95%CI, 0.41–0.85; P = 0.004; I 2 = 68%) and PFS (pooled HR, 0.43; 95%CI, 0.36–0.52; P < 0.00001; I 2 = 50%) compared with patients who did not have skin irAEs ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective data and meta-analyses for single-agent ICB across multiple tumor sites have largely observed improved objective response rates, progression-free survival, and OS among patients who develop irAEs. [7][8][9][10][11] In metastatic melanoma, the association of irAEs with outcomes has been more variable. 7,12,13 One proposed explanation may be immortal time bias, in particular in early studies.…”
Section: Introductionmentioning
confidence: 99%
“…In an adjuvant setting, and for melanoma patients, Eggermont et al were also able to demonstrate a correlation between irAEs and an improvement in recurrence-free survival (RFS) [ 8 ]. In contrast to reports based on data from clinical studies, this relationship has not been studied as intensively in real-world data [ 23 ]. This work describes the association of the occurrence of immune-related adverse events and improved survival in melanoma using real-world data.…”
Section: Introductionmentioning
confidence: 99%